1977
DOI: 10.1007/bf02533633
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐phosphatidic acid in developing soybeans and soybean suspension cultures

Abstract: A phospholipid which rapidly accumulates radioactivity from [1‐14C] acetate administered to slices of developing soybeans or to suspension cultures of soybean cells was isolated. Its structure was identified by comparison of its properties and degradation products with those of authentic lipid standards using infrared absorption spectrometry, thin layer chromatography, acetolysis, mild alkaline hydrolysis, and determination of molar ratios of phosphorus, glycerol, and acyl moieties. The structure of the phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since PG accounted for 3-5% of the total phospholipid in our preparations and the recovery of pure BPA suggested a similar proportion for that lipid in the work of Stearns and Morton (4), this could be another case of mistaken identity. One piece of circumstantial evidence favoring this possibility is that BPA was undetectable in mature seeds (4). If the lipid was really PG, then this would be consistent with the virtual disappearance of the other plastid membrane lipids, monogalactosyl and digalactosyl diacylglycerols, at ripening (2).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since PG accounted for 3-5% of the total phospholipid in our preparations and the recovery of pure BPA suggested a similar proportion for that lipid in the work of Stearns and Morton (4), this could be another case of mistaken identity. One piece of circumstantial evidence favoring this possibility is that BPA was undetectable in mature seeds (4). If the lipid was really PG, then this would be consistent with the virtual disappearance of the other plastid membrane lipids, monogalactosyl and digalactosyl diacylglycerols, at ripening (2).…”
Section: Discussionmentioning
confidence: 91%
“…Soybeans which were analyzed without prior freezing and thawing apparently contained N-acyl phosphatidylethanolamine (NAPE) at levels as high as 65% of the total phospholipid (3). More recently, it has been suggested that the identification of NAPE may have been erroneous and that bis-phosphatidic acid (BPA) instead accounts for 30-40% of the total phospholipid in very immature soybean seeds (4). The latter, it was reported, has chromatographic mobilities similar to those of NAPE.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relatively large amounts of PA in immature soybeans appears to be artifacts of handling and extraction procedures as suggested by Roughan et al (4). It also appears that contamination with PM formed by transphosphatidylation of PC and PE with methanol in conventional chloroform-methanol extraction procedures could account for the reports of large amounts of bis-phosphatidic acid (10) (14), to remove the organicsoluble, nonlipid substances. Sephadex chromatography is t i m e -c o n s u m i n g and removes the highly polar glycolipids as well as the nonlipid substances.…”
Section: Discussionmentioning
confidence: 99%